Conceptual Hydraulic Conductivity Model for Unsaturated Soils at Low Degree of Saturation and Its Application to the Study of Capillary Barrier Systems - Scarfone, Riccardo; Wheeler, Simon J.; Lloret-Cabot, Marti (Journal of Geotechnical and Geoenvironmental Engineering, 2020)
Accurate modeling and prediction of the variation of the hydraulic conductivity of unsaturated soils at a very low degree of saturation has important implications in various engineering problems. Physical processes underlying the hydraulic behavior of unsaturated soils (retention behavior and variation of hydraulic conductivity) are first explained, and then a consistent set of new definitions for key transition hydraulic states is proposed. This lays the foundation for the presentation of a new predictive hydraulic conductivity model, accurate for the full range of degree of saturation and applicable to relatively coarse-grained soils (i.e., gravels, sands, and silts). The hydraulic conductivity is divided into two components—a bulk water component and a liquid film component—each of which varies with the degree of saturation or suction. The model is then validated against experimental data. Finally, the new hydraulic conductivity model is applied to the numerical study of the hydraulic behavior of capillary barrier systems (CBSs). The new model is able to predict the behavior of CBSs better than conventional models, and the numerical modeling highlights the role of liquid film flow, which is often neglected.
EPrint Processing Status: Full text deposited in DRO